The relationship between overhydration, increased oxidative stress and peritoneal dialysis adequacy - Stepanova, N.; Korol, L.; Burdeyna, O.; Snisar, L. (Ukrainian Journal of Nephrology and Dialysis, 2019)
The present study was undertaken to investigate the association of hydration status measured by bioimpedance analysis with oxidative stress biomarkers and peritoneal dialysis (PD) adequacy. Methods. It was a case-control study involved 85 PD patients from 2 dialysis centers in Ukraine. Among the examined patients, there were 56/85 (65.9%) men and 29/85 (34.1%) women. All patients had been undergoing PD for more than 3 months (median was 25.4 [14.0-49.5] months). Average age was 48.8 ± 12.5 years. Fluid compartments [extracellular water (ECW) and overhydration index (OH)] were measured using Multifrequency bio-impedance (BCM®, Fresenius Medical Care, Germany). Overhydration was defined as OH/ECW> 15%. Malondialdehyde concentration in serum (MDAs) and erythrocytes (MDAe) was defined as an indicator of lipid peroxidation. Such parameters as the concentration of ceruloplasmin (CP), transferrin (TR) and sulfhydryl groups (SH-groups) in the blood and total peroxidase activity in erythrocyte (TPAe) were studied as the indicators of antioxidant system. Moreover, to determine the intraperitoneal oxidative stress induction, we studied MDA and TPO in PD effluent. Results. Among 85 PD participants, there were 38(44.7%) patients in normohydration range and 47 (55.3%) overhydrated pаtients according to the OH/ECW ratio. There were a significant increase in serum and PD effluent MDA (p = 0.01 and p = 0.001, respectively) in overhydrated PD patients whereas the concentrations of serum CP and TPA in PD effluent were significantly lower compared with normohydrated patients (p = 0.008 and p = 0.04, respectively). In addition, ECW had an inverse correlation with SH-groups (r = -0.37; p = 0.003) and MDAs (r = -0.48; p = 0.004). An odds ratio of PD inadequacy was 3.6 times higher among overhydrated patients than in normovolemic one: OR = 3.6 (95% CI 1.3-10.3; p = 0.01). Conclusions. Extracellular fluid overload promotes intraperitoneal and systemic oxidative stress which could be one of the pathway explanations of technique survival failure and cardiovascular mortality in overhydrated PD patients.